Management Tactics in Patients with Postoperative Ventral Hernia and Obesity - Khaydarova L.O (Genius Journals, 2023)
Obesity is one of the reasons worsening the results of hernioplasty. The urgency of the problem of surgical correction of abdominal deformities in patients with excessive body weight is caused not only by a large number of complications of early and late postoperative period, recurrences, but also by uncertainty in tactic and methodological approaches. Also, patients with morbid obesity have high intra-abdominal pressure in comparison with patients without obesity.
Keywords: Ventral hernia; abdominopotosis; surgical treatment